Self-perception, complaints and vocal quality among undergraduate students enrolled in a Pedagogy course - Fabron, Eliana Maria Gradim [UNESP]; Regaçone, Simone Fiuza [UNESP]; Marino, Viviane Cristina de Castro [UNESP]; Mastria, Marina Ludovico [UNESP]; Motonaga, Suely Mayumi [UNESP]; Sebastião, Luciana Tavares [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2015)
To compare the vocal self-perception and vocal complaints reported by two groups of students of the pedagogy course (freshmen and graduates); to relate the vocal self-perception to the vocal complaints for these groups; and to compare the voice quality of the students from these groups through perceptual auditory assessment and acoustic analysis. METHODS: Initially, 89 students from the pedagogy course answered a questionnaire about self-perceived voice quality and vocal complaints. In a second phase, auditory-perceptual evaluation and acoustic analyses of 48 participants were made through voice recordings of sustained vowel emission and poem reading. RESULTS: The most reported vocal complaints were fatigue while using the voice, sore throat, effort to speak, irritation or burning in the throat, hoarseness, tightness in the neck, and variations of voice throughout the day. There was a higher occurrence of complaints from graduates than from freshmen, with significant differences for four of the nine complaints. It was also possible to observe the relationship between vocal self-perception and complaints reported by these students. No significant differences were observed in the results of auditory-perceptual evaluation; however, some graduates had their voices evaluated with higher severity of deviation of normalcy. During acoustic analysis no difference was observed between groups. CONCLUSION: The increase in vocal demand by the graduates may have caused the greatest number and diversity of vocal complaints, and several of them are related to the self-assessment of voice quality. The auditory-perceptual evaluation and acoustic analysis showed no deviations in their voice.

Comparar a autopercepção vocal e as queixas vocais reportadas por dois grupos de alunas do curso de Pedagogia (ingressantes e formandas); relacionar a autopercepção vocal com as queixas vocais nesses grupos e comparar a qualidade vocal das alunas desses grupos por meio da avaliação perceptivo-auditiva e da análise acústica. MÉTODOS: Inicialmente, 89 estudantes de um curso de Pedagogia responderam a um questionário sobre a autopercepção da qualidade vocal e queixas vocais. Numa segunda etapa foram realizadas análises perceptivo-auditiva e acústica das vozes de 48 participantes, por meio de gravações de emissão de vogal sustentada e leitura de poema. RESULTADOS: As queixas vocais mais relatadas foram cansaço no uso da voz, dor na garganta, esforço para falar, irritação ou ardor na garganta, rouquidão, tensão na nuca e variações da voz ao longo do dia. Houve maior ocorrência de queixas entre as formandas, quando comparadas com as ingressantes, mas com diferença significativa para quatro das nove queixas. Também foi possível observar a relação entre a autopercepção vocal e as referidas queixas dessas alunas. Não foram encontradas diferenças significativas nos resultados da análise perceptivo-auditiva, entretanto, algumas formandas tiveram suas vozes avaliadas com maior severidade de desvio da normalidade. Na análise acústica não houve diferença entre os grupos. CONCLUSÃO: O aumento da demanda vocal pelas formandas pode ter provocado o maior número e diversidade de queixas vocais, sendo que várias delas se relacionaram com a autoavaliação da qualidade vocal. As avaliações perceptivo-auditiva e acústica não mostraram desvios na voz.
Autopercepção, queixas e qualidade vocal entre discentes de um curso de Pedagogia
Keywords: Voice; Voice Disorders; Voice Quality; Evaluation; Self-assessment; Voz; Distúrbios da Voz; Qualidade da Voz; Avaliação; Autoavaliação